Is Technology Enhancing or Hindering Interpersonal Communication? A Framework and Preliminary Results to Examine the Relationship Between Technology Use and Nonverbal Decoding Skill - Ruben, Mollie A.; Stosic, Morgan D.; Correale, Jessica; Blanch-Hartigan, Danielle (Frontiers in Psychology, 2021)
Digital technology has facilitated additional means for human communication, allowing social connections across communities, cultures, and continents. However, little is known about the effect these communication technologies have on the ability to accurately recognize and utilize nonverbal behavior cues. We present two competing theories, which suggest 1) the potential for technology use to enhance nonverbal decoding skill or, 2) the potential for technology use to hinder nonverbal decoding skill. We present preliminary evidence from two studies to test these hypotheses. Study 1 (N = 410) found that global screen time was unrelated to nonverbal decoding skill. However, how participants spent their time using technology mattered. Participants who reported more active technology use (i.e. posting content) self-reported that their nonverbal decoding skill was superior but performed worse on objective measures of decoding skill. By contrast, passive users performed significantly better on objective measures of nonverbal decoding skill; although they did not self-report any difference in their skill compared to less passive users. Study 2 (N = 190), and a mini-meta analysis of both studies, replicated this pattern. These effects suggest a roadmap for understanding the theoretical relationship between technology use and nonverbal communication skills. We also provide recommendations for future research, including the use of experimental designs to determine causal pathways and to advance our conceptual understanding of the relationship between technology use and nonverbal decoding skill.